Inaugurated Hyperspace - Page, Ben ca. 20./21. Jh. (TheoLogica, 2021)
Several philosophers of religion have used contemporary work on the metaphysics of space to dismantle objections to Christian doctrine. In this paper I shall also make use of work in the metaphysics of space to explore a topic in Christian thought that has received little attention by philosophers, namely inaugurated eschatology. My aim will be to take the conclusions of some biblical scholars who have written on this topic, and then begin to provide some metaphysical models of this doctrine, so as to overcome objections against inaugurated eschatology based on metaphysical concerns.